2009
DOI: 10.1002/9780471729259.mca03hs15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Staining of Bacteria: Acid Fast Stain

Abstract: Acid‐fastness is an uncommon characteristic shared by the genera Mycobacterium (Section 10A) and Nocardia. Because of this feature, this stain is extremely helpful in identification of these bacteria. Although Gram positive, acid‐fast bacteria do not take the crystal violet into the wall well, appearing very light purple rather than the deep purple of normal Gram‐positive bacteria. Curr. Protoc. Microbiol. 15:A.3H.1‐A.3H.5. © 2009 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The present study reported S-I culture when exposed with different antibiotics on MRS agar, was shown to be resistant to ampicillin (10 mcg), chloramphenicol (25 mcg), streptomycin (10 mcg), sulphatried (300 mcg), tetracycline (25 mcg), and penicillin-G (1 unit) (Fig. 8) as per the interpretation of zones of inhibition for Kirby-Bauer antibiotic susceptibility test as reported in (Reynolds et al, 2009).…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 69%
“…The present study reported S-I culture when exposed with different antibiotics on MRS agar, was shown to be resistant to ampicillin (10 mcg), chloramphenicol (25 mcg), streptomycin (10 mcg), sulphatried (300 mcg), tetracycline (25 mcg), and penicillin-G (1 unit) (Fig. 8) as per the interpretation of zones of inhibition for Kirby-Bauer antibiotic susceptibility test as reported in (Reynolds et al, 2009).…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 69%
“…Several acid-fast staining techniques are available, such as the older Ziehl-Neelsen stain and newer fluorescent stains with improved sensitivity (46). Of note, acid-fast staining occurs in both M tuberculosis complex and nontuberculous mycobacteria, as well as a number of other bacterial organisms, including Nocardia organisms (47). The sensitivity of the smear for AFB with three successive expectorated sputum specimens is 68%-72% in patients with culture-positive tuberculosis (48)(49)(50) and 62% in HIV-positive patients (48).…”
Section: Stainingmentioning
confidence: 99%
“…Only mycobacteria have been reported resistant to crystal violet. Mycobacteria are classified acid fast Gram-positive, but typically do not retain the crystal violet stain (Reynolds et al., 2009). It is because mycobacteria can absorb crystal violet into lipid cell fractions which causes decolorization of crystal violet (Jones and Falkinham, 2003; Coban, 2014).…”
Section: Discussionmentioning
confidence: 99%